Ecological Agency through Language Learning: An Eco-CLA Assessment of Climate-Focused Activities in Low-Resource Contexts - Syahfitri, Dian; Siregar, Arianto (Studia Ecologiae et Bioethicae, 2026)
This study examines whether climate-focused language activities develop environmental awareness alone or also foster critical consciousness of environmental injustice. We analyzed ten CALE activities using the Eco-CLA framework, which assesses climate-language integration across five pedagogical principles. Results show significant asymmetry. Activities excel at concrete environmental engagement, sustainability framing, and localization—grounding language learning in students' lived experiences. But justice advocacy and linguistic pluralism receive inconsistent treatment. Students develop environmental awareness without necessarily gaining critical consciousness of injustice or seeing their linguistic diversity validated. CALE activities offer accessible, pedagogically sound materials for resource-limited contexts. Yet transformative climate education demands additional work. Teachers need to supplement these materials with critical pedagogy that interrogates environmental injustice, power structures, and linguistic ideologies. Most teacher preparation programs fail to systematically develop these competencies. Indonesian educators face compounded challenges: classes of 35-40 students, relentless standardized testing pressures, and minimal institutional support for critical approaches. Individual teacher effort cannot overcome these barriers. The Eco-CLA framework gives teachers a diagnostic tool to identify where activities work well and where they must intervene with critical pedagogical approaches.